2002
DOI: 10.1097/00129492-200209000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation for Adolescents and Adults with Prelinguistic Deafness

Abstract: The results of this study indicate that individuals with long-term prelinguistic deafness can achieve significant open-set speech understanding with a cochlear implant, although there is a wide range of performance across patients. The results ranged from 0% to 74% for words and 0% to 98% for sentences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 9 publications
9
66
1
5
Order By: Relevance
“…Indeed studies published so far agree about the poorer performances of prelingually deafened adolescents or adults compared to postlingually deafened or early implanted subjects [Bassim et al, 2005;Manrique et al, 1999;Schramm et al, 2002;Snik et al, 1997;Teoh et al, 2004a;Waltzman et al, 2002]. Nevertheless, different degrees of improvement in speech perception scores on closed-set tests have been reported by various studies, while openset speech recognition performances vary from null to a moderate increase after cochlear implantation.…”
Section: Introductionmentioning
confidence: 94%
“…Indeed studies published so far agree about the poorer performances of prelingually deafened adolescents or adults compared to postlingually deafened or early implanted subjects [Bassim et al, 2005;Manrique et al, 1999;Schramm et al, 2002;Snik et al, 1997;Teoh et al, 2004a;Waltzman et al, 2002]. Nevertheless, different degrees of improvement in speech perception scores on closed-set tests have been reported by various studies, while openset speech recognition performances vary from null to a moderate increase after cochlear implantation.…”
Section: Introductionmentioning
confidence: 94%
“…The early studies of adult recipients with prelinguistic hearing loss showed only limited improvement in speech perception skills after implantation [Dawson et al, 1992;Skinner et al, 1992;Waltzmann et al, 1992;Zwolan et al, 1996]. More recent research, however, has found a greater range of improvement, with the considerable variability in outcome partly explained by differences in duration of hearing loss and age at time of implantation [Sarant et al, 1994;Schramm et al, 2002;Teoh et al, 2004;Waltzmann and Cohen, 1999]. Among postlinguistically deafened adult CI recipients, the strongest predictors of success appear to be age at onset of hearing loss [Kaplan et al, 2003], duration of hearing loss [Blamey et al, 1996;Geier et al, 1999;Hamzavi et al, 2003, Oh et al, 2003Shea et al, 1990; UK Cochlear Implant Study Group, 2004] and age at implantation [Blamey et al, 1996;Tyler and Summerfield, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…The research that is available focused mainly on audiological outcomes. Improvements such as an increased awareness of environmental sounds, better speech discrimination and better speech perception without lip-reading have all been reported, including in those teenagers who were pre-lingually deafened (Kiefer et al, 1996;Schramm et al, 2002;Sarant et al, 1994). This is encouraging since prelingual deafness (being deafened before language is acquired) can be associated with poorer outcomes compared with post-lingual deafness, if there is a delay in implanting the child.…”
Section: List Of Figuresmentioning
confidence: 99%
“…The speech and language abilities of pre-lingually deafened teenagers were reported to be good following implantation in early adolescence (Kiefer et al, 1996;Schramm et al, 2002;Sarant et al, 1994). However, there is variation between individuals and very small numbers of adolescents were studied which makes it difficult to assess how representative these conclusions are.…”
Section: Speech and Language Developmentmentioning
confidence: 99%
See 1 more Smart Citation